2021
DOI: 10.1371/journal.pone.0248120
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on vegetable supply chain and food security: Empirical evidence from Bangladesh

Abstract: In Bangladesh, the COVID-19 pandemic is likely to have substantial effects on the livelihood of people, but smallholder vegetables growers will be even more affected because of the perishability nature of the product. The first case of COVID-19 was confirmed in Bangladesh on 8th March, 2020 and consequently the country went into lockdown on 26 March, 2020. This study has made a survey of vegetables farmers through a mobile phone to understand the impact of COVID-19 on vegetables supply chain, gross margin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 14 publications
1
52
0
1
Order By: Relevance
“…A survey study in Bangladesh (Malek et al, 2021) supported the findings where authors found that during COVID-19 period, the rural economy experienced adverse impacts, with delayed harvest, difficulty in selling farm produce, input disruptions, and cost increases. Another study (Alam & Khatun, 2021) also stated that decrease farmers' income enhanced the likelihood of vulnerability and posed a challenge to continue their produce which is similar to the study finding.…”
Section: Usd 298 Millionsupporting
confidence: 80%
“…A survey study in Bangladesh (Malek et al, 2021) supported the findings where authors found that during COVID-19 period, the rural economy experienced adverse impacts, with delayed harvest, difficulty in selling farm produce, input disruptions, and cost increases. Another study (Alam & Khatun, 2021) also stated that decrease farmers' income enhanced the likelihood of vulnerability and posed a challenge to continue their produce which is similar to the study finding.…”
Section: Usd 298 Millionsupporting
confidence: 80%
“…The frequent food safety incidents and scandals in the Chinese food market, including the emergence of COVID-19, have increased the greater concerns of the sojourners with regard to food safety during their sojourning in China (Leone et al, 2020 ). During the emergence of COVID-19, the foodservice operators were among those who experienced the direct impact of the pandemic, which caused the potential source of infection (Aday and Aday, 2020 ). These types of concerns are consistent with food safety and are very important for food preferences.…”
Section: Aims and Hypothesismentioning
confidence: 99%
“…Restrictions of movement of goods (e.g., border restrictions; export restrictions; import restrictions) [7,10,14,[27][28][29]33,[36][37][38]48,52,58,70,[73][74][75][76][78][79][80][81][82][83][84]89,99,107,111,113,[115][116][117][118]123,127,131,137,[139][140][141][142][146][147][148][149]152,157,158,163,165,…”
Section: Logistics Disruptionsmentioning
confidence: 99%
“…Food distribution disruption [1,13,29,36,37,50,57,58,60,66,67,[71][72][73]75,79,80,84,92,100,106,108,118,136,140,142,171,183] Decision support tools Decision Support System (DSS) [3] Online infrastructures E-delivery services; online platforms [8,135] Transportation and distribution plans Short-term incentives for distributors [61] Distribution planning and resource allocation [14] Strengthening food storage and inter-and intra-island transport [171] Distribution strategy [67] Government financial assistance for companies Government humanitarian assistance [29,140] Reduction of fees and taxes [66,84,113] Government purchasing agricultural products from small farmers and shorter supply chains [84] Restructuring plans Emergency cashflow and liquidity measures [93] Significant funds [29] Activate the agricultural crisis reserve …”
Section: Logistics Disruptionsmentioning
confidence: 99%
See 1 more Smart Citation